Procesos didácticos y pensamiento matemático en niños de la Institución Educativa Inicial N°728, Caballococha 2024 - Guerra Sugaya, Genifer Sandra (2024)
The objective of the research was to determine the relationship between the level of application of didactic processes and the level of mathematical thinking in children of the Initial Educational Institution N°728, Caballo Cocha 2024. In this research, Quantitative research, in terms of the type of research, was relational, the "correlational and transactional" design, the population studied was made up of all the children of the Initial Educational Institution No. 728, which adds up to a total of 88 children. Observation was used as a technique; and as an instrument an observation guide. For validity, they were evaluated by a team of experts, and reliability has been validated by the Cronbach Alpha test. The results obtained showed a student’s t statistical value of 8,577 and a p-value (bilateral significance) of 0,000. Since the significance value is less than 0,05, it was decided to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) with a significance level of 5%. This leads to the conclusion that there is a significant relationship between the implementation of didactic processes and the development of mathematical thinking in children.